Metamorphosis into mother after 35 years of age: a study of Grounded Theory - Maria Anabela Ferreira dos Santos; Maria dos Anjos Pereira Lopes; Maria Antónia Rebelo Botelho
ABSTRACT Objective To understand the transition process of women through maternity status after 35 years of age. Method The methodology of constructivist Grounded Theory was used in the design of research, data collection and analysis. Results The results allowed the construction of a comprehensive model of the transition to motherhood experience after the age of 35, called "Metamorphosis in Mother". This process integrates several categories, being addressed in this article only two of them: "Confronting the dark side" and "Caring for herself". Conclusion From the results, the difficulties experienced by the mothers around the 2nd month are highlighted, which revealed an obscure side of motherhood unknown to mothers and the need to take care of themselves to overcome these difficulties.